Optymistyczne podejście do życia jako czynnik ochronny dla nastolatków z LD i ADHD - Wizman-Man , Dikla (Studia Edukacyjne, 2018)
The objective of this study is to examine the influenceof life-stories narrative intervention programs on the optimistic approach towards life of adolescents with learning disabilities (LD) and attention deficitdisorders (ADHD). Changes in the optimistic approach towards life of adolescents with LD and ADHD who took part in an intervention program were compared pre-and post-program and to ordinary high school graduates who did not participate in the program. The findingsindicate a significantimprovement in the level of optimism pre- and post- intervention program. In addition, higher levels of optimistic approach towards life in the general index and relating to graduates’ level of optimism in situations of uncertainties were reported among graduates with LD and ADHD, compared with regular high school graduates. No differences were found in other aspects of the questionnaires. Results call for further research on additional protective variables, and on the effectiveness of the intervention program in both special education and regular high schools.